Are They Really a New Species? Exploring the Emergence of Social Entrepreneurs Through Giddens's Structuration Theory. Issue 7 (September 2022) - Steiner, Artur; Jack, Sarah; Farmer, Jane; Steinerowska-Streb, Izabella
Using Giddens's structuration theory and empirical data from a study with social enterprise stakeholders, the article explores how social entrepreneurs and the structure co-create one another. We show that the development of the contemporary significance of social entrepreneurialism lies in a combination of complex context-specific structural forces and the activities of agents who initiate, demand, and impose change. Social entrepreneurs intentionally tackle social challenges, but their actions bring unintentional results, such as the transfer of state responsibilities onto communities. Direct outputs of their activities introduce indirect outcomes, bringing wider changes in culture and policy. The evolving nature of entrepreneurship and a number of factors that interplay in time and space, and enable and constrain social entrepreneurs, confirm the applicability of Giddens's theory in the field of social entrepreneurship. The originality of this article derives from revealing mechanisms that enable social entrepreneurs to emerge and reasons for structural change. We also build a "co-creation model of structure and agency" that can be used to "engineer" the process of social entrepreneurship.